Determinants of Consumer Buying Interest in Traditional Retail Stores in Medan - Afrida Yanti Surbakti; Bertha Nerpy Siahaan; Sarman Sinaga; Monang Tarigan; Ika Julianti Silveria Br Pandiangan (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to analyze the effect of price, location, product quality, and service quality on consumer purchasing interest in purchasing basic necessities. Data were collected through a questionnaire method distributed to 120 respondents who shopped at a Medan grocery store. Sample selection was carried out using a simple random sampling technique to obtain respondents' responses related to the research variables. Furthermore, the data were analyzed quantitatively using validity tests, reliability, multiple linear regression analysis, F test, t test, and determination coefficient analysis (R²). The results of hypothesis testing using the t test showed that the three independent variables (price, location, product quality, and service quality) had a significance value of less than 0.05, namely price of 0.001, location of 0.001, product quality of 0.581, and service quality of 0.001. Meanwhile, the results of the F test indicated that simultaneously, the variables price, location, product quality, and service quality had a significant effect on consumer purchasing interest with a significance level of 0.001. Based on the results of the determination coefficient analysis, it was found that 65.1% of the variation in consumer purchasing interest can be explained by the variables of price, location, product quality, and service quality, while the remaining 34.9% is influenced by other factors not included in this study. Keywords : Price, Location, Product, Service, Purchase Interest